2015
DOI: 10.1002/cne.23723
|View full text |Cite
|
Sign up to set email alerts
|

Retinal projections in the short‐tailed fruit bat, Carollia perspicillata, as studied using the axonal transport of cholera toxin B subunit: Comparison with mouse

Abstract: To provide a modern description of the Chiropteran visual system, the subcortical retinal projections were studied in the short-tailed fruit bat, Carollia perspicillata, using the anterograde transport of eye-injected cholera toxin B subunit, supplemented by the silver-impregnation of anterograde degeneration following eye removal, and compared with the retinal projections of the mouse. The retinal projections were heavily labeled by the transported toxin in both species. Almost all components of the murine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 78 publications
(197 reference statements)
3
16
0
Order By: Relevance
“…The IGL of the flat-faced fruit-eating bat receives a bilateral retinal projection and the OD analysis indicates possible symmetrical innervation. This configuration was visualized in the short-tailed fruit bat ( Scalia et al, 2015 ) (Supplementary Table S2 ). Differently from present work, a predominantly contralateral projection was described in Nile grass rat ( Negroni et al, 2003 ), degu ( Goel et al, 1999 ), and California ground squirrel ( Major et al, 2003 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The IGL of the flat-faced fruit-eating bat receives a bilateral retinal projection and the OD analysis indicates possible symmetrical innervation. This configuration was visualized in the short-tailed fruit bat ( Scalia et al, 2015 ) (Supplementary Table S2 ). Differently from present work, a predominantly contralateral projection was described in Nile grass rat ( Negroni et al, 2003 ), degu ( Goel et al, 1999 ), and California ground squirrel ( Major et al, 2003 ).…”
Section: Discussionmentioning
confidence: 90%
“…Nocturnal species developed perceptive senses of smell and hearing and concentrate their activity in the dark phase of the cycle ( Sousa and Menezes, 2006 ). Some animals, such as bats, have developed additional specializations (echolocation and flying), which allow them to exploit the environment and forage for food ( Simmons, 1989 ; Scalia et al, 2015 ). Chiropterans are exclusively or almost exclusively nocturnal ( Rydell and Speakman, 1995 ), and their daily patterns of activity and behavior are influenced principally by components of the light/dark cycle, such as dusk, dawn ( Erket, 1982 ), light intensity ( Haeussler and Erkert, 1978 ), moonlight ( Apple et al, 2017 ) and night length ( Frafjord, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The morphologic results demonstrated that CTB displayed RGC neurites, including axons, more clearly than FG, although the specific reason for this remains unclear. We conjecture that it is due to the tracers’ individual natures; indeed, CTB is suitable for use both as a retrograde and an anterograde tracer [ 28 , 35 , 36 ], whereas FG can only be utilized as a retrograde tracer [ 27 ]. This means that CTB may be transported from cell bodies to cell processes and thereby stain neurites more clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, CTB is selectively taken up into the cytoplasm by adsorptive endocytosis [ 35 ]. In fact, CTB can also be used as an anterograde tracer [ 28 , 35 , 36 ], whereas FG can only be utilized as a retrograde tracer [ 27 ]. FG was first utilized as a retrograde fluorescent tracer by Schmued and Fallon [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microchiroptera have no (Pettigrew, 1986b) or very few IRP (Scalia et al, 2015). Fruit bats, Megachiroptera, which commonly use claws on the wing to climb trees and manipulate fruit (Zhang et al, 2010), possess a primate-like visual system with a large proportion of IRP and an extensively developed primary visual area (Pettigrew, 1986b;Rosa et al, 1993).…”
Section: Mammalsmentioning
confidence: 99%